Increased Frequency of Memory CD4+ T-Cell Responses in Individuals With Previously Treated Extrapulmonary Tuberculosis - Barreto-Duarte, Beatriz; Sterling, Timothy R.; Fiske, Christina T.; Almeida, Alexandre; Nochowicz, Cynthia H.; Smith, Rita M.; Barnett, Louise; Warren, Christian; Blackman, Amondrea; Lapa e Silva, Jose Roberto; Andrade, Bruno B.; Kalams, Spyros A. (Frontiers in Immunology, 2020)
Extrapulmonary TB (EPTB) occurs with increased frequency in persons with underlying immunodeficiency. Even after recovery from acute illness, differences in immune phenotype and activation persist. Studies defining characteristics of immune responses after recovery from extrapulmonary TB may provide insights into factors that increase TB risk. We performed two case-control studies (in the United States and Brazil) among HIV-seronegative adults with previous EPTB (n=9;25), previous pulmonary TB (n=7;25), latent Mycobacterium tuberculosis (Mtb) infection (n=11;25), and uninfected TB contacts (n=10;25). We assessed the frequency of dual CD4+ interferon-γ and tumor necrosis factor-α responses after stimulation with overlapping Mtb peptides from ESAT-6 or CFP-10, or gamma-irradiated Mtb H37Rv, proliferative responses to Mtb antigens, T-regulatory cell (Treg) frequency and phenotype. In both study populations, individuals with prior EPTB had the highest frequency of intracellular cytokine-producing cells in response to Mtb antigens (p<0.05;p<.0001). Persons with prior EPTB in Brazil had the highest levels of CD4 proliferation to Mtb antigens (p<0.0001), and the highest expression of CD39 on Tregs (p<0.0001). Individuals with treated EPTB maintained high frequencies of Mtb-specific memory responses and active Treg cells, suggesting that susceptibility to EPTB occurs despite the ability to develop and maintain enhanced adaptive immune responses.